Using florbetapir positron emission tomography to explore cerebrospinal fluid cut points and gray zones in small sample sizes. Issue 4 (2nd November 2015) - Weston, Philip S.J.; Paterson, Ross W.; Modat, Marc; Burgos, Ninon; Cardoso, Manuel J.; Magdalinou, Nadia; Lehmann, Manja; Dickson, John C.; Barnes, Anna; Bomanji, Jamshed B.; Kayani, Irfan; Cash, David M.; et al.
Abstract: Introduction: We aimed to assess the feasibility of determining Alzheimer's disease cerebrospinal fluid (CSF) cut points in small samples through comparison with amyloid positron emission tomography (PET). Methods: Twenty‐three individuals (19 patients, four controls) had CSF measures of amyloid beta (Aβ)1–42 and total tau/Aβ1–42 ratio, and florbetapir PET. We compared CSF measures with visual and quantitative (standardized uptake value ratio [SUVR]) PET measures of amyloid. Results: Seventeen of 23 were amyloid‐positive on visual reads, and 14 of 23 at an SUVR of ≥1.1. There was concordance (positive/negative on both measures) in 20 of 23, of whom 19 of 20 were correctly classified at an Aβ1–42 of 630 ng/L, and 20 of 20 on tau/Aβ1–42 ratio (positive ≥0.88; negative ≤0.34). Three discordant cases had Aβ1–42 levels between 403 and 729 ng/L and tau/Aβ1–42 ratios of 0.54–0.58. Discussion: Comparing amyloid PET and CSF biomarkers provides a means of assessing CSF cut points in vivo, and can be applied to small sample sizes. CSF tau/Aβ1–42 ratio appears robust at predicting amyloid status, although there are gray zones where there remains diagnostic uncertainty.